2007
DOI: 10.1097/01.aog.0000258298.35143.d2
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and Misoprostol Administered Simultaneously Versus 24 Hours Apart for Abortion

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 31 publications
1
73
0
2
Order By: Relevance
“…With a regimen of mifepristone and vaginal misoprostol, approximately 3% to 5% of women will subsequently undergo uterine evacuation [1][2][3]. Regimens using mifepristone and buccal misoprostol have a similar (3.3%) risk of requiring uterine evacuation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With a regimen of mifepristone and vaginal misoprostol, approximately 3% to 5% of women will subsequently undergo uterine evacuation [1][2][3]. Regimens using mifepristone and buccal misoprostol have a similar (3.3%) risk of requiring uterine evacuation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the data collected on 16 000 women who had been treated with 600 mg of mifepristone followed by a prostaglandin analogue 24-72 hours later suggested that the efficacy was highest if the interval was 48 hours. 9 Different time intervals between mifepristone and misoprostol have also been tested 10 or both drugs have been administered simultaneously, 11 repeating the dose of misoprostol if abortion was not complete. When misoprostol was not repeated, complete abortion rates seem to be significantly lower with shorter intervals.…”
Section: Introductionmentioning
confidence: 99%
“…similar success rate has been shown by studies conducted by Crenin et al (94%). 11 Scaff et al, the advantage of medical abortion is that it has high efficacy at gestational age ≤49 days. 13 This study emphasizes on proper selection of patients by using various inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%